If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3(4x + 3) = 2 Reorder the terms: 5 + -3(3 + 4x) = 2 5 + (3 * -3 + 4x * -3) = 2 5 + (-9 + -12x) = 2 Combine like terms: 5 + -9 = -4 -4 + -12x = 2 Solving -4 + -12x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -12x = 2 + 4 Combine like terms: -4 + 4 = 0 0 + -12x = 2 + 4 -12x = 2 + 4 Combine like terms: 2 + 4 = 6 -12x = 6 Divide each side by '-12'. x = -0.5 Simplifying x = -0.5
| -(-2n-4)=5(n+2) | | 36=-9(10+1) | | 23=14+4n | | 5y^2+14=14 | | -(7n+1)-5(n+7)=12 | | 12+1.5x=15+.5 | | (7t-2)-(-3t+1)=-3-9t | | 3.5-0.02x=1.46 | | (-3)-(-14)=x | | 5x^2-25x-120=0 | | 3(u+w)+-5(u-w)= | | a(4-x)=0 | | 2x-4=8+4x | | 5(t-1)+2(t-1)=-2(t-2)+10(t+2) | | 4.9t^2+3t=5.2 | | 5*5.25=(k*5.75)+(5-k*4.50) | | 21+3*(2x-2)-2x=60-x | | 9y-2x=-11 | | 3(x+2)=2(3-x) | | 4(m+1)+7(-m+8)=75 | | 6+3x+3=15 | | y(y-7)-6=2 | | 2x+1+x+4= | | p=3t+2w | | 5n+3n=-12 | | -6(-2v+8)=5(-5v+5)+1 | | 2x-120=180 | | 8d^2+2d= | | -15.00+2.00x=-1 | | 3m-2(m-3)=3 | | 24=3x+6y | | 0.34x+5=9 |